Patient experience of different regional models of urgent and emergency care: a cross-sectional survey study. Issue 3 (20th March 2017) - Foley, Conor; Droog, Elsa; Boyce, Maria; Healy, Orla; Browne, John
Abstract : Objectives: To compare user experiences of 8 regional urgent and emergency care systems in the Republic of Ireland, and explore potential avenues for improvement. Design: A cross-sectional survey. Setting: Several distinct models of urgent and emergency care operate in Ireland, as system reconfiguration has been implemented in some regions but not others. The Urgent Care System Questionnaire was used to explore service users' experiences with urgent and emergency care. Linear regression and logistic regression were used to detect regional variation in each of the 3 domains and overall ratings of care. Participants: A nationally representative sample (N=8002) of the general population was contacted by telephone, yielding 1205 participants who self-identified as having used urgent and emergency care services in the previous 3 months. Main outcome measures: Patient experience was assessed across 3 domains: entry into the system, progress through the system and patient convenience of the system . Participants were also asked to provide an overall rating of the care they received. Results: Service users in Dublin North East gave lower ratings on the entry into the system scale than those in Dublin South (adjusted mean difference=−0.18; 95% CI −0.35 to −0.10; p=0.038). For overall ratings of care, service users in the Mid-West were less likely than those in Dublin North East to give an excellent rating (adjusted OR 0.57; 95% CI 0.35 to 0.92; p=0.022). Survey items relating to communication, and consideration of patients' needs were comparatively poorly rated. The use of public emergency departments and out-of-hours general practice care was associated with poorer patient experiences. Conclusions: No consistent relationship was found between the type of urgent and emergency care model in different regions and patient experience. Scale-level data may not offer a useful metric for exploring the impact of system-level service change.